2018
DOI: 10.1111/jcmm.13637
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1‐mediated vasculogenic mimicry formation associates with epithelial–mesenchymal transition and cancer stem cell phenotypes in prostate cancer

Abstract: The zinc finger E‐box‐binding homeobox 1 (ZEB1) induced the epithelial–mesenchymal transition (EMT) and altered ZEB1 expression could lead to aggressive and cancer stem cell (CSC) phenotypes in various cancers. Tissue specimens from 96 prostate cancer patients were collected for immunohistochemistry and CD34/periodic acid–Schiff double staining. Prostate cancer cells were subjected to ZEB1 knockdown or overexpression and assessment of the effects on vasculogenic mimicry formation in vitro and in vivo. The unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 55 publications
2
24
0
1
Order By: Relevance
“…Similarly, the high level of ZEB1, another EMT-related transcription factor, was strongly associated with the presence of VM in 96 prostate cancer samples (P < 0.05) 37. Similarly, the high level of ZEB1, another EMT-related transcription factor, was strongly associated with the presence of VM in 96 prostate cancer samples (P < 0.05) 37.…”
mentioning
confidence: 86%
“…Similarly, the high level of ZEB1, another EMT-related transcription factor, was strongly associated with the presence of VM in 96 prostate cancer samples (P < 0.05) 37. Similarly, the high level of ZEB1, another EMT-related transcription factor, was strongly associated with the presence of VM in 96 prostate cancer samples (P < 0.05) 37.…”
mentioning
confidence: 86%
“…VE-cadherin is a VM biomarker and plays a crucial role in the process of VM formation [23,43]. Some EMT-associated transcription factors including Snail1, Slug (Snail2) [45], Zinc finger E-box binding homeobox 1 (ZEB1) [18,46], ZEB2 [13] and Twist1 [11]. These transcription factors can bind to the E-cadherin promoter to regulate transcriptional activity, and the decreased levels of E-cadherin result in decreased cell adhesion and increased cell invasion and metastasis [22,30].…”
Section: Epithelial-mesenchymal Transition and Vmmentioning
confidence: 99%
“…Additionally, in prostate cancer, ZEB1 regulates VM formation and alters the expression of CSC-associated protein CD133. Furthermore, the follow-up experiments revealed that ZEB1 knockdown reduces the level of p-Src [527], the results showed ZEB1 is essential to CSC phenotype and VM formation by Src signaling [18]. Recently, in hepatocellular carcinoma, Zhao et al found that LncRNA n339260 promotes VM formation in HCC by inducing CSC-like phenotype and the knockdown of n339260 reduced VM and CSCs.…”
Section: Tumor Microenvironment and Vm Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, tumor cells associated to VM structures acquire an undifferentiated phenotype as well as ECs characteristics (80). Nowadays, CSCs have been involved in VC formation in cancer (81)(82)(83)(84)(85)(86)(87). For instance, in salivary adenoid cystic carcinoma (ACC) specimens CD133 is positively associated with VM formation.…”
Section: Vasculogenic Mimicry Formation By Cscs In Gastrointestinal Cmentioning
confidence: 99%